Recensione di C. D’Essì, M. Floris, Le imprese familiari. Fisionomia di un fenomeno in evoluzione, Franco Angeli, Milano, 2017. - Conti, Emanuela (Piccola Impresa / Small Business, 2021)
This book proposes a new perspective to analyze the heterogeneous world of family businesses, applying the Psychological Ownership Theory which allows family business members to attribute meaning – sensemaking – to this kind of business. In particular, it systematizes the literature in an original way and suggests an innovative conceptual framework/definition of family business consisting of a founding part, common to all these businesses, and a dynamic part, unique for every business. This book may be useful for scholars, managers, students and family business members themselves.